Peculiarities of human pancreatolienal hemolymph node structure and cellular composition. - Pototskaya, O. Yu.; Lapsar, H. S. (Морфологія / Morphologia / Morfologìâ, 2016)
Background. Hemolymph nodes (HLNs) are well described in animals, while in humans they are still poorly characterized; little is known about the role of HLNs in red blood cells destruction, erythropoiesis, iron metabolism etc. Objective. To determine the peculiarities of HLN structure and cellular composition. Methods. Pancreatolienal HLNs were taken during autopsy from patients who died due to cardiovascular or respiratory pathology. Standard histological and histochemical methods were used to detect iron, bile components, lipofuscin. Results. Inside afferent vessels of HLNs equal numbers of red and white blood cells were found. The same ratio was in subcapsular and cortical sinuses, while in medullary sinus erytrhrocytes were absent. Some RBCs enter lymphoid follicles through opened blood capillaries. Inside HLNs parenchyma large lipofuscin-laden cells are frequently observed, by their staining properties they resemble sea-blue histiocytes found under normal circumstances in red bone marrow. Conclusions. HLNs receive mixture of blood and lymph; during circulation through the system of sinuses all erythrocytes are destroyed via phagocytosis by local macrophages. During hemoglobin degradation these macrophages release iron outside, but undigested membranes of RBCs undergo lipid peroxidation giving rise to lipofuscin stored inside the cell.